An entity access control model for network services management - Dias, Bruno (2005)
The Network Services Management Framework tries to overcome the most important limitations of present network management frameworks, namely the most widely supported framework – the Internet Network Management Framework – by defining a management framework using a network services management distributed architecture that provides services management functions with any desired level of functionality. This document introduces one of the most important parts of this framework, the Entity Access Control Model and the mechanisms needed to its deployment: management entities and management domains, entity access and resources control management, and security mechanisms (authentication, data integrity verification, confidentiality and non-repudiation assurances). This model, although originally developed to be integrated on the Network Services Management Framework, can be completely integrated or partially adopted by other frameworks since it supports a wide range of conceptual and functional requisites recognised to be fundamental to the future of modern distributed network management frameworks.